Multiple cranial neuropathies in Churg-Strauss syndrome: case report - G. Rutkauskaitė; R. Masaitienė; J. Dadonienė; D. Jatužis (Neurologijos seminarai)
Churg-Strauss syndrome (CSS), known as eosinophilic granulomatosis with polyangiitis, is a systemic small- to medium-sized vasculitis, characterized by chronic rhinosinusitis, asthma and eosinophilia. Churg and Strauss first described this syndrome in 1951. Histology of CSS usually discloses eosinophil-rich infiltrates, necrotising vasculitis, and eosinophilic-granulomatous inflammation. There are no clear pathophysiologic mechanisms that explain the development of CSS but association between CSS and HLA-DRB4 has been reported. Because of the frequent positivity of antineutrophil cytoplasmic antibodies (ANCAs), which are found in 30–40% of the cases, CSS has been grouped with ANCA-associated vasculitis. Nervous system manifestations are found in up to 70% of CSS patients, while cranial neuropathies are rarely diagnosed. Patients are treated with glucocorticoids and immunosuppressants. We describe a case report of a 68-year-old woman with a clinical diagnosis of Churg-Strauss syndrome and multiple cranial neuropathies.